2013
DOI: 10.4161/onci.25156
|View full text |Cite
|
Sign up to set email alerts
|

VEGFA/VEGFR2-targeted therapies prevent the VEGFA-induced proliferation of regulatory T cells in cancer

Abstract: Some of the anti-angiogenic agents currently used to treat solid malignancies have effects on tumor endothelial cells as well as on immune cells. We have recently demonstrated that targeting the vascular endothelial growth factor A (VEGFA)/VEGF receptor 2 (VEGFR2) signaling pathway reduces the proportion of regulatory T cells (Treg) in a mouse model of colorectal cancer (CRC) and in metastatic CRC patients as it inhibits tumor-induced Treg proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 10 publications
(11 reference statements)
0
23
0
Order By: Relevance
“…In addition, VEGF can limit T cell extravasation and induce expansion of Treg populations, thereby further enhancing the immunosuppressive state. 34,[54][55][56] It is, therefore, reasonable to expect that inhibition of the VEGF/VEGFR-2 axis would reverse tumor-mediated immunosuppression or enhance the effects of immunostimulatory antitumor therapies. 31,34,36 In contrast with these observations, however, experimental data show that anti-angiogenic therapy also mobilizes MDSC, which in turn can limit the therapeutic benefit of anti-angiogenic therapy, 26,29,31 and in certain tumor models may even exacerbate metastatic progression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, VEGF can limit T cell extravasation and induce expansion of Treg populations, thereby further enhancing the immunosuppressive state. 34,[54][55][56] It is, therefore, reasonable to expect that inhibition of the VEGF/VEGFR-2 axis would reverse tumor-mediated immunosuppression or enhance the effects of immunostimulatory antitumor therapies. 31,34,36 In contrast with these observations, however, experimental data show that anti-angiogenic therapy also mobilizes MDSC, which in turn can limit the therapeutic benefit of anti-angiogenic therapy, 26,29,31 and in certain tumor models may even exacerbate metastatic progression.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that TGF-β and VEGF-A are potent immunosuppressive factors that drive the expansion of regulatory T-cells and myeloid-derived suppressor cells (37). Moreover, platelets also contain proteins such as thrombospondin-1 (TSP-1) and CD40L.…”
Section: Figure 3 Sequential Changes In Blood Sample Values At 6 H mentioning
confidence: 99%
“…T‐cell tolerance through natural or induced pathways of self‐tolerance generation appears to be the most difficult one and this represents a significant challenge to successful cancer immunotherapy. To achieve an effective anti‐tumour response, therapeutic vaccines must be capable of overcoming or reversing T‐cell tolerance to tumour antigens whether it is via naturally occurring CD4 + CD25 + Treg cells or by induced Treg cells (induced from CD4 + CD25 − cells) . We have shown that tumour‐specific CTL generated in vitro from total PBL declined within 2–3 weeks with a concomitant expansion of suppressor type CD4 + cells .…”
Section: The Possibilities To Circumvent Treg Cell‐based Constraintsmentioning
confidence: 90%
“…Anti‐angiogenic agents that are used to treat solid tumours have effects on tumour endothelial cells as well as on immune cells. Targeting the VEGFA/VEGF receptor 2 (VEGFR2) signalling pathway reduces the proportion of Treg cells in mouse as well as human colorectal cancer because it inhibits tumour‐induced Treg cell proliferation . Similarly it has been found that the TLR7/8L:CL097 could simultaneously activate CD8 + T cells, B cells and natural killer cells and block Treg cell suppression of T cells and B cells …”
Section: The Possibilities To Circumvent Treg Cell‐based Constraintsmentioning
confidence: 99%